Peran Perpustakaan Lembaga Pemasyarakatan Klas I Malang dalam meningkatkan literasi informasi narapidana - Karina Okta Bella; Mutia Indriyani; Chamdi Fajar (Jurnal Kajian Informasi dan Perpustakaan, 2019)
Information literacy is a social capital for today's millennials as information literacy can make a difference for a better life. Every individual has the right to obtain and use information, including inmates. However, inmates have limited access to information while in prison; not all useful information can be obtained easily. Based on this fact, research on the role of libraries in improving prisoners' information literacy at the Correctional Institution Class I in Malang is essential to determine the library’s influence on prisoners' information literacy. The purpose of this study was to find out about the role of the library in improving prisoner’s information literacy. This study used the descriptive qualitative method with a qualitative approach. The data collection techniques through interviews, observation, and study literature. Study results indicated that the Library of the Correctional Institution Class I in Malang had a role as the primary source of information, a place for creating, and a place that provides learning activities for inmates. Information literacy at the Correctional Institution Class I in Malang applies local wisdom which is not carried out by other specialized libraries, such as library staff that does not have library science education backgrounds, the library collection contains religious, folklore, general knowledge, and skill books. The library’s role in improving information literacy of prisoners can be seen from the works produced by the inmates, such as paintings, plant cultivation, and books that tell about their daily lives in prison. Information literacy is a social capital for today's millennials as information literacy can make a difference for a better life. Every individual has the right to obtain and use information, including inmates. However, inmates have limited access to information while in prison; not all useful information can be obtained easily. Based on this fact, research on the role of libraries in improving prisoners' information literacy at the Correctional Institution Class I in Malang is essential to determine the library’s influence on prisoners' information literacy. The purpose of this study was to find out about the role of the library in improving prisoner’s information literacy. This study used the descriptive qualitative method with a qualitative approach. The data collection techniques through interviews, observation, and study literature. Study results indicated that the Library of the Correctional Institution Class I in Malang had a role as the primary source of information, a place for creating, and a place that provides learning activities for inmates. Information literacy at the Correctional Institution Class I in Malang applies local wisdom which is not carried out by other specialized libraries, such as library staff that does not have library science education backgrounds, the library collection contains religious, folklore, general knowledge, and skill books. The library’s role in improving information literacy of prisoners can be seen from the works produced by the inmates, such as paintings, plant cultivation, and books that tell about their daily lives in prison.